Oral Dispersible Tablets - A Review - P.Venkateshwar Reddy,; Swagata Dutta Roy,; G.Vasavi,; N.Sriram, (International Journal of Pharmacy and Analytical Research, 2014)
The convenience of administration and improved patients compliance are important in the design of oral drug delivery s system which remains the preferred route of drug delivery inspite of various disadvantage.one such problem can be solved in the novel drug delivery system by formulating oral disintegrating tablets which disintegrates rapidly without water within few seconds in the mouth due to action of super disintegrants in the formulation. Oral disintegrating tablets are advantageous for pediatric, geriatric mentally ill, nausea patients who have difficulty in swallowing conventional tablets and capsules. Using various excipients, evaluation tests marketed formulation and drugs used in the research area.